Drop formation at a hole in a plate submerged in quiescent continuous phase: comparison of plain hole and nozzle hole. Issue 10 (3rd October 2019) - Sen, Nirvik; Singh, K. K.; Mukhopadhyay, S.; Shenoy, K. T.
Abstract: The phenomenon of drop formation at a single plain hole and a single nozzle hole in a plate submerged in a quiescent continuous phase is studied by carrying out numerical simulations. Phase-field method has been used for tracking the evolution of the interface between the drop phase and the continuous phase. The computational approach used in the numerical simulations is validated using the data reported in literature. The validated computational approach is then used for parametric analysis to understand the effects of various independent variables on the phenomenon of drop formation. For identical conditions, the drops formed at a nozzle hole are found to be smaller than the drops formed at a plain hole. The drop detachment time is more for a plain hole than for a nozzle hole. The drop detachment height is, however, more for a nozzle hole than for a plain hole. Correlations to estimate drop diameter for both types of holes are presented.